Compositions, thermodynamic properties, and transport coefficients of high-temperature C5F10O mixed with CO2 and O2 as substitutes for SF6 to reduce global warming potential - Zhong, Linlin; Rong, Mingzhe; Wang, Xiaohua; Wu, Junhui; Han, Guiquan; Han, Guohui; Lu, Yanhui; Yang, Aijun; Wu, Yi (AIP advances, 2017)
C5F10O has recently been found to be a very promising alternative to SF6. This paper is devoted to the investigation of compositions, thermodynamic properties, and transport coefficients of high-temperature C5F10O mixed with CO2 and O2. Firstly, the partition functions and enthalpies of formation for a few molecules (CxFy and CxFyO) which are likely to exist in the mixtures, are calculated based on the G4(MP2) theory. The isomers of the above molecules are selected according to their Gibbs energy. The compositions of C5F10O-CO2-O2 mixtures are then determined using the minimization of the Gibbs free energy. Next, the thermodynamic properties (mass density, specific enthalpy, and specific heat) are derived from the previously calculated compositions. Lastly, the transport coefficients (electrical conductivity, viscosity, and thermal conductivity) are calculated based on Chapman-Enskog method. It is found that, as an arc quenching gas, C5F10O could not recombine into itself with the temperature decreasing down to room temperature after the arc extinction. Besides, the key species at room temperature are always CF4, CO2, and C4F6 if graphite is not considered. When taken into account, graphite will replace C4F6 as one of the dominate particles. The mixing of CO2 with C5F10O plasma significantly affects the thermodynamic properties (e.g. vanishing and/or shifting of the peaks in specific heat) and transport coefficients (e.g. reducing viscosity and changing the number of peaks in thermal conductivity), while the addition of O2 with C5F10O-CO2 mixtures has no remarkable influence on both thermodynamic and transport properties.